2023
DOI: 10.1029/2023gl104090
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Short Observational Record on the Statistics of Temperature Extremes

Joel Zeder,
Sebastian Sippel,
Olivier C. Pasche
et al.

Abstract: In June 2021, the Pacific Northwest experienced a heatwave that broke all previous records. Estimated return levels based on observations up to the year before the event suggested that reaching such high temperatures is not possible in today's climate. We here assess the suitability of the prevalent statistical approach by analyzing extreme temperature events in climate model large ensemble and synthetic extreme value data. We demonstrate that the method is subject to biases, as high return levels are generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Results depend weakly on the covariate dataset used (ERA5 or GISTEMP, see figure 1). We note however an overestimation of the estimated RP compared to the actual RP, which becomes significant when RPs greater than 50 years are considered: this is probably partly due to estimation of RPs higher than the length of the time series, and partly due to the known tendency of maximum likelihood estimation to over-estimate return times (Zeder et al 2023). We found that from 1950-1979 (prior to the satellite era), in some regions with few observation data (parts of South America and Africa), a large number of extreme events with high RPs was found (see also figure 2).…”
Section: Resultsmentioning
confidence: 74%
“…Results depend weakly on the covariate dataset used (ERA5 or GISTEMP, see figure 1). We note however an overestimation of the estimated RP compared to the actual RP, which becomes significant when RPs greater than 50 years are considered: this is probably partly due to estimation of RPs higher than the length of the time series, and partly due to the known tendency of maximum likelihood estimation to over-estimate return times (Zeder et al 2023). We found that from 1950-1979 (prior to the satellite era), in some regions with few observation data (parts of South America and Africa), a large number of extreme events with high RPs was found (see also figure 2).…”
Section: Resultsmentioning
confidence: 74%
“…It is a common practice in event attribution studies to perform "out of sample" statistical analyses where the event in question (often the maximum value in the observations) is excluded. It has recently been pointed out that this can introduce a selection bias (Miralles and Davison, 2023;Zeder et al, 2023). However, it can be the case that the maxima in question can be far outliers and cause very poor quality of fit for the rest of the extreme value sample data if included in the fitting data (Bercos-Hickey et al, 2022) casting doubts on the validity of the attribution statements.…”
Section: Discussionmentioning
confidence: 99%
“…Here we see, besides the remarkably high agreement of the empirical and analytical latitudinal patterns, that analytical probability ratios tend to be slightly lower. This might be explained by the limitations of GEV-fits in representing the highest end of the tail, especially if the sample size is modest [40].…”
Section: Global Precipitation Record Shattering Probability Increases...mentioning
confidence: 99%